Spiritual Needs among Patients with Mental Disorders: A Scoping Review - Suryani, Suryani; Rafiyah, Imas (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The problem of mental disorders is currently an unresolved health problem, mental status that is not handled properly has the potential to cause relapse in people with mental disorders (ODGJ). Spiritual needs as human needs such as ODGJ patients that are fulfilled can provide strength in facing a problem. The purpose of this study is to explore the spiritual needs of patients with mental disorders. The design in this study used scoping review. Keywords used are "Patient with Mental Disorders" AND "Spirituality" OR "Spiritual Needs" OR "Spiritual Care". The results showed that there were 13 articles analyzed that showed a good level of spirituality in ODGJ, but their spirituality needs had not been met. The spiritual level of people with mental disorders is in the medium - low range. Mental health well-being includes an experience of connection with oneself, connection with others, with nature and connection with the transcendent. Spirituality can help overcome mental health problems by expressing trust in God for healing and health. It is recommended that nurses are able to pay attention to aspects of spiritual needs in spiritual-centered mental health care services not only focus on providing drugs.